DISCERNMENT, ETHICS AND THE BIBLE - Byrne, Patrick (Science et Esprit, 2023)
This essay discusses the relationship between Ethics and the Bible and draws on Lonergan to show how the Torah understood as “Teaching” promotes an “ethics of discernment” rather than an ethics of law and obedience. It shows how Lonergan’s approach to Method in Theology points to a synthesis between the work of critical-historical Biblical scholarship and the exercise that Ignatius of Loyola called “composition of place.”